International Normalized Ratio (INR) Increases amongst Two Patients Living with HIV on Warfarin after Being Switched from a Nevirapine to a Dolutegravir-Based Antiretroviral Regimen - Natalie Sang; Sonak Pastakia; Samuel Nyanje (Case Reports in Infectious Diseases)
The increased use of dolutegravir-based regimens in the treatment of HIV is unmasking drug interactions, particularly in patients who were previously on nevirapine. Nevirapine is an enzyme inducer and increases the dosing requirements for cytochrome P450 enzyme substrates including warfarin. Upon discontinuing nevirapine, close monitoring of drugs with narrow therapeutic indices is paramount since dosing requirements may significantly reduce, increasing the probability of toxicity development. We present two cases describing interactions experienced by patients living with HIV, while transitioning from nevirapine to dolutegravir-based HIV regimens. The first case describes a 70-year-old man living with HIV and diabetes, while the second case describes a 60-year-old woman living with HIV. They were diagnosed with unprovoked deep vein thrombi, and while receiving treatment with warfarin, their HIV medication regimen was changed from lamivudine, zidovudine, nevirapine, and septrin to lamivudine, tenofovir, dolutegravir, and septrin. During the weeks following this switch, warfarin requirements decreased resulting in supratherapeutic INRs. With the continued promotion of dolutegravir-based HIV regimens as the preferred option for the treatment of HIV in President’s Emergency Plan for AIDS Relief (PEPFAR) supported HIV treatment programs in Africa, clinicians must be aware of the potentially life-threatening consequences of switching antiretroviral regimens. It is hoped that a greater awareness of this potential side effect could lead to increased monitoring and prevention of the consequences of drug interactions.